2008
DOI: 10.1158/0008-5472.can-08-1444
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition Induced by Growth Suppressor p12CDK2-AP1 Promotes Tumor Cell Local Invasion but Suppresses Distant Colony Growth

Abstract: Epithelial-mesenchymal transition (EMT) has been considered essential for metastasis, a multistep process including local invasion, intravasation, extravasation, and proliferation at distant sites. However, controversy remains as to whether EMT truly happens and how important it is to metastasis. We studied the involvement of EMT in individual steps of metastasis and found that p12, a down-stream effector of transforming growth factor B, induced EMT of hamster cheek pouch carcinoma-1 cells by promoting the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
180
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(196 citation statements)
references
References 45 publications
15
180
1
Order By: Relevance
“…-induced EMT of hamster cheek pouch carcinoma-I cells (Tsuji et al, 2008). Twist2 mRNA is overexpressed in a large variety of human primary tumours; however, the transcriptional expression pattern of Twist2 differs from that of Twist1 in some of these cancers .…”
Section: Cdk2àap1mentioning
confidence: 96%
“…-induced EMT of hamster cheek pouch carcinoma-I cells (Tsuji et al, 2008). Twist2 mRNA is overexpressed in a large variety of human primary tumours; however, the transcriptional expression pattern of Twist2 differs from that of Twist1 in some of these cancers .…”
Section: Cdk2àap1mentioning
confidence: 96%
“…5B; Mateo et al 2014). In addition, heterotypic interactions among EMT and non-EMT cells have also been demonstrated to increase metastasis progression of hamster cheek pouch carcinoma cells (Tsuji et al 2008) as well as in xenograft models of prostate cancer metastasis (Celia-Terrassa et al 2012). In the latter study, both clonal populations seeded distant organs, although only the non-EMT clonal population-enriched in epithelial-like CSCs-expanded to overt metastases.…”
Section: Clonal Cooperationmentioning
confidence: 99%
“…Comparing sublines of the T24-TSU-Pr1 human bladder carcinoma cell line, Chaffer et al (2006) have shown that cells displaying rather epithelial characteristics are more metastatic when intracardiac injection are performed, whereas they form less metastases when injected s.c.. In another work, Tsuji et al (2008) developed a model of hamster oral keratinocytes (HPCP-1) transformed in vitro by a downstream effector of the TGF-b pathway (p12 CKD2ÀAP1 ), which consequently caused EMT traits. Following s.c. injection in mice, the authors found that only p12 CKD2ÀAP1 EMT þ cells were able to reach the blood vessels, in agreement with our observations supporting the involvement of EMT in intravasation.…”
Section: Emt In Ctc and Metastasis Formationmentioning
confidence: 99%
“…injections were performed, the authors found that only non-EMT cells developed lung metastases. Furthermore, Tsuji et al (2008Tsuji et al ( , 2009 reported cooperativity when co-inoculation of the two cell sublines was performed, resulting in lung metastases comprising only non-EMT cells . Though our observations do not exclude the possibility that such cooperation exist in humans, our system allowing dynamic plasticity (induction and reversion of EMT), showing that all cells found in emboli are vimentin-positive, suggest at least that such cooperation is not necessary in all systems.…”
Section: Emt In Ctc and Metastasis Formationmentioning
confidence: 99%